The Diagnostic Value of Inflammatory Markers (CRP, IL6, CRP/IL6, CRP/L, LCR) for Assessing the Severity of COVID-19 Symptoms Based on the MEWS and Predicting the Risk of Mortality - Wolszczak-Biedrzycka B; Dorf J; Milewska A; Łukaszyk M; Naumnik W; Kosidło JW; Dymicka-Piekarska V (Dove Medical Press, 2023)
Blanka Wolszczak-Biedrzycka,1 Justyna Dorf,2 Anna Milewska,3 Mateusz Łukaszyk,4 Wojciech Naumnik,4 Jakub Wiktor Kosidło,5 Violetta Dymicka-Piekarska2 1Department of Psychology and Sociology of Health and Public Health, University of Warmia and Mazury in Olsztyn, Olsztyn, 10-082, Poland; 2Department of Clinical Laboratory Diagnostics, Medical University of Bialystok, Bialystok, 15-269, Poland; 3Department of Biostatistics and Medical Informatics, Medical University of Bialystok, Bialystok, 15-295, Poland; 4Temporary Hospital No 2 of Clinical Hospital in Bialystok, 1 St Department of Lung Diseases and Tuberculosis, Medical University of Bialystok, Bialystok, 15-540, Poland; 5Students Scientific Club at the Department of Clinical Laboratory Diagnostics, Medical University of Bialystok, Bialystok, 15-269, PolandCorrespondence: Blanka Wolszczak-Biedrzycka, Department of Psychology and Sociology of Health and Public Health, University of Warmia and Mazury in Olsztyn, Olsztyn, 10-082, Poland, Email blanka.wolszczak@gmail.comIntroduction: Various diagnostic tools are used to assess the severity of COVID-19 symptoms and the risk of mortality, including laboratory tests and scoring indices such as the Modified Early Warning Score (MEWS). The diagnostic value of inflammatory markers for assessing patients with different severity of COVID-19 symptoms according to the MEWS was evaluated in this study.Materials and Methods: The concentrations of CRP (C-reactive protein) (immunoassay) and IL6 (interleukin 6) (electrochemiluminescence assay) were determined, and CRP/IL6, CRP/L, and LCR ratios were calculated in blood serum samples collected from 374 COVID-19 patients.Results: We demonstrated that CRP, IL6, CRP/IL6, CRP/L, LCR inflammatory markers increase significantly with disease progression assessed based on the MEWS in COVID-19 patients and may be used to differentiating patients with severe and non-severe COVID-19 and to assess the mortality.Conclusion: The diagnostic value of inflammatory markers for assessing the risk of mortality and differentiating between patients with mild and severe COVID-19 was confirmed.Keywords: COVID-19, CRP, C-reactive protein, IL-6, interleukin 6, inflammatory markers, MEWS, modified early warning score